Review of Researching language learning motivation: A concise guide by Ali H. Al-Hoorie and Fruzsina Szabó - Li, Zixuan (Studies in Second Language Learning and Teaching, 2022)
In the context of buoyant research on second language acquisition (SLA), language learning motivation has remained one of the most active fields of inquiry for more than 60 years (Al-Hoorie & MacIntyre, 2019; Ushioda, 2019). Several books have approached this topic from a range of perspectives (e.g., Dörnyei & Ushioda, 2021; Lamb et al., 2019; MacIntyre & Al-Hoorie, 2020). However, the seemingly unceasing theoretical and methodological innovation in motivation research can be confusing, and it has become increasingly overwhelming to keep abreast of all the latest advancements in this burgeoning field. In response to this “promising” yet “perplexing” situation, Ali H. Al-Hoorie and Fruzsina Szabó have edited the volume Researching language learning motivation: A concise guide, presenting a timely guidebook for both students and novice researchers to navigate their way through the journey of language learning motivation.